2014
DOI: 10.1021/ja5007299
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Domain Swaps of Iterative, Nonreducing Polyketide Synthases Provide a Mechanistic Understanding and Rationale For Catalytic Reprogramming

Abstract: Iterative, nonreducing polyketide synthases (NR-PKSs) are multidomain enzymes responsible for the construction of the core architecture of aromatic polyketide natural products in fungi. Engineering these enzymes for the production of non-native metabolites has been a long-standing goal. We conducted a systematic survey of in vitro “domain swapped” NR-PKSs using an enzyme deconstruction approach. The NR-PKSs were dissected into mono- to multidomain fragments and recombined as noncognate pairs in vitro, reconsti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 43 publications
6
67
0
Order By: Relevance
“…This finding was in complete accord with similar comparisons of intact vs . domain combinations determined recently, and confirms the validity of the deconstruction method for the purposes of the experiments described herein(19). …”
Section: Resultssupporting
confidence: 89%
“…This finding was in complete accord with similar comparisons of intact vs . domain combinations determined recently, and confirms the validity of the deconstruction method for the purposes of the experiments described herein(19). …”
Section: Resultssupporting
confidence: 89%
“…From a matrix of six NR-PKSs enzyme components we have found that ACPs are substantially interchangeable; maintaining SAT–KS pairs is beneficial to overall synthetic efficiency; chain length is largely, but not exclusively, determined by the KS with occasional participation by the PT; PT active sites are unexpectedly accommodating with respect to the chain lengths of the polyketide intermediates presented to them, yet the regiochemistry of their cyclizations is tightly controlled; and, as noted above, the TE is crucial to success. Enzyme-directed cyclizations must outpace spontaneous reaction and TE-mediated editing, 52, 53 but “rules” have emerged from these studies where rapid combinatorial experiments can be used to quickly survey potential heterodomain combinations for assembly into single PKS chimeras for more efficient synthesis. 53 …”
Section: Behaviour and Engineering Of Nr-pkssmentioning
confidence: 99%
“…Enzyme-directed cyclizations must outpace spontaneous reaction and TE-mediated editing, 52, 53 but “rules” have emerged from these studies where rapid combinatorial experiments can be used to quickly survey potential heterodomain combinations for assembly into single PKS chimeras for more efficient synthesis. 53 …”
Section: Behaviour and Engineering Of Nr-pkssmentioning
confidence: 99%
“…The present results have therefore verified the success of this study for accessing novel chemical space. A number of methods based on PKS engineering have been developed and have produced diverse unnatural polyketide molecules [37][38][39][40][41][42] . These methods are undoubtedly powerful enough to generate analogues of structurally complex metabolites, although they do have some weakness regarding the simultaneous expansion of molecular frameworks.…”
Section: Discussionmentioning
confidence: 99%